Relationship Between Locus Of Control, Paranormal Beliefs, And Magical Ideation Among Young Adults Of Pakistan - Malik, Rozia; Akhtar, Shammem; Mughal, Fatima Ali Raza (Journal of Rawalpindi Medical College, 2024)
Objective: Para normality, often seen as violating fundamental scientific principles, includes beliefs in phenomena such as spirits, extrasensory perception, and fortune telling. These extraordinary beliefs are linked to belief. Locus of control (LOC), which refers to an individual's perception of control as internal or external, is a well-studied concept. This study aimed to explore the relationship between locus of control, paranormal beliefs, and magical ideation in early adulthood, and to examine how individual differences affect these variables. Methods: A sample of 142 college and university students aged 18-25 were selected using a convenience sampling technique through social media platforms like Facebook and WhatsApp, due to COVID-19 and quarantine restrictions. The Multidimensional Locus of Control Scale (MLOCS), Paranormal Belief Scale, and Magical Ideation Scale were utilized for data collection. The data were analyzed using SPSS (26 version) Results: Descriptive analysis for demographic variables and correlation analysis showed that locus of control positively correlated with internal LOC (ILOC), external LOC (ELOC), and paranormal beliefs, but negatively with magical ideation. Specifically, ILOC was positively correlated with paranormal beliefs and negatively with magical ideation, while ELOC showed the same pattern. Paranormal beliefs were negatively correlated with magical ideation. An independent sample t-test revealed no significant gender differences. Conclusion: The study highlights the complex relationships between religiosity, locus of control, and superstitious beliefs. Although there may be a link between religiosity and superstitious belief, this connection is not straightforward. A limitation of the study is the reliance on a convenience sample from social media, which may not be fully representative of the broader population. Keywords: Locus of Control, Paranormal-Beliefs, Magical Thinking, Superstitions, Religiosity, Social Media, Quarantine.